Fully understanding the efficacy profile of the COVID-19 vaccination and its associated factors in multiple real-world settings - Panahi, Yunes; Einollahi, Behzad; Beiraghdar, Fatemeh; Darvishi, Mohammad; Fathi, Saeid; Javanbakht, Mohammad; Shafiee, Sepehr; Akhavan-Sigari, Reza (Frontiers in Immunology, 2022)
We performed a review study according to recent COVID-19 vaccines’ real-world data to provide comparisons between COVID-19 vaccines regarding their relative efficacy. Although most vaccine platforms showed comparable effectiveness and efficacy, we highlight critical points and recent developments generated in studies that might affect vaccine efficacy including population-dependent effects of the vaccine (transplantation, adiposity, and specific comorbidities, as well as older age, male sex, ethnicity, and prior infection), vaccine type, variants of concern (VOC), and an extended vaccine schedule. Owing to these factors, community-based trials can be of great importance in determining vaccine effectiveness in a systematic manner; thus, uncertainty remains regarding vaccine efficacy. Long immune protection of vaccination with BNT162b2 or ChAdOx1 nCoV-19 has been demonstrated to be up to 61 months and 5–12 months after the previous infection, and boosting infection-acquired immunity for both the first and second doses of the BNT162b2 and ChAdOx1 nCoV-19 vaccines was correlated with high and durable protection. However, large cohort and longitudinal studies are required for the evaluation of immunity dynamics and longevity in unvaccinated, vaccinated, and infected individuals, as well as vaccinated convalescent individuals in real-world settings. Regarding the likelihood of vaccine escape variants evolving, an ongoing examination of the protection conferred against an evolving virus (new variant) by an extended schedule can be crucial.